Effects of Two Different Doses of Zinc Sulfate on Serum Troponin I 3 Enzyme Level and Cardiac Malondialdehyde Contents in Mitoxantrone-Induced Cardiotoxicity in Rats - Taif M. Maryoosh; Nada N. Al-Shawi; Eman S. Salih (College of Pharmacy University of Baghdad, 2020)
Abstract    Mitoxantrone is an antitumor agent used in the treatment of breast and prostate cancer, acute leukemia, lymphoma, and also in the treatment of multiple sclerosis due to its immunosuppressive properties. The mitoxantrone's cardiotoxicity is irreversible, dose-dependent, and it may occur years after treatment. Zinc is considered as an essential mineral for cell division and the synthesis of DNA and protein; furthermore, such mineral has an important role in states of cardiovascular diseases; and may have protective effects in coronary artery disease and cardiomyopathy. Objective: The current study is designed to investigate effects of two different doses of zinc sulfate on mitoxantrone-induced cardiotoxicity in rats. Methods: Forty-eight (48) adult rats of both sexes were utilized in this study; the animals were randomly divided into six groups of 8 animals each. Group I: distilled water (negative control). Group II: orally-administered zinc sulfate (15mg/kg/day) Group III: orally-administered zinc sulfate (30mg/kg/day) Group IV: Intraperitoneally injected with a mitoxantrone at a dose (2.5 mg/kg) to reach total cumulative dose of 7.5 mg/kg on day 20. Group V: Orally-administered zinc sulfate at a dose (15mg/kg/day) and an intraperitoneal injection of mitoxantrone at a dose (2.5 mg/kg) was administered to reach total cumulative dose of 7.5 mg/kg on day 20. Group VI: Orally-administered zinc sulfate at a dose (30 mg/kg/day), and an intraperitoneal injection of mitoxantrone at a dose (2.5 mg/kg) to reach total cumulative dose of 7.5 mg/kg on day 20. Forty-eight (48) hr after the end of treatment duration (i.e. at day 22 nd), each animal was euthanized by diethyl ether and ketamine. Then, after cervical dislocation, blood was obtained by intracardiac puncture and then serum was prepared to estimate cardiac troponin I 3 enzyme activity levels; and the heart of each animal was excised for homogenate preparation to estimate of malondialdehyde contents. Results: Oral administration of zinc sulfate [(15mg/kg/day with total cumulative dose (7.5 mg/kg) of mitoxantrone] (Group V) resulted in a non-significant (P>0.05) difference in serum activity level of troponin I 3 enzyme and malondialdehyde contents in cardiac tissue homogenate compared to the corresponding serum enzyme activity level and contents in group of rats intraperitoneally injected with total cumulative dose of 7.5 mg/kg of mitoxantrone (Group IV). In contrast, there were significant reduction (P<0.05) in serum activity level of troponin I 3 enzyme and malondialdehyde contents in cardiac tissue homogenate of rats orally-administered zinc sulfate [(30 mg/kg/day) with total cumulative dose (7.5mg/kg) of mitoxantrone] (Group VI) compared to the corresponding enzyme activity levels and contents in group of rats intraperitoneally-injected with total cumulative dose of 7.5mg/kg of mitoxantrone (Group IV). Conclusion: zinc sulfate at a dose (30 mg/kg/day) diminishes the cardiotoxicity induced by mitoxantrone via a free radical scavenger property but it is non signifant compared to (15 mg/kg/day) .